EFEKTIVITAS PENERAPAN PROGRESSIVE MUSCLE RELAXATION DAN GUIDED IMAGERY TERHADAP KELELAHAN PADA PASIEN KANKER YANG MENJALANI KEMOTERAPI DI RUMAH SAKIT REGIONAL WILAYAH INDONESIA TIMUR - Nurul Rezki Anisa (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2018)
Introduction: Chemotherapy is one of the most popular cancer treatments that has been used effectively to the patients of cancer nowadays. However, it has many side effects of physical and psychological of patients that contribute to the quality of life. One of the side effect is fatigue. The combination Progressive muscle relaxation (PMR) and guided imagery (GI) is one of the nursing interventions that leads patient to be relaxed by muscles contracting-releasing process. The purpose of this study was to identify the effect of PMR and GI on fatigue scale of cancer patients undergoing chemotherapy. Method: This study used aquasi-experimental study with pre-test and post-test design. The instrument of this study using a questionnaire of fatigue scale. Sample in this study were 11 patients of cancer undergoing chemotherapy. Statistical test used was Friedman test with significance level ?=0.05. Result: The result was obtained a day after intervention. Analysis showed bivariate relationship between intervention and fatigue scale p=0.0001(p>?). Conclusions: There is a significant effect of progressive muscle relaxation and guided imagery to decrease fatigue of cancer patients undergoing chemotherapy. Therefore, the training of progressive muscle relaxation and guided imagery should be recommended to the nurses in hospital as a nursing intervention for helping cancer patients reduce the effect of chemotherapy. This study is recommended a further study using more samples